Regulation of Photosynthetic Induction State by the Magnitude and Duration of Low Light Exposure. - Sassenrath-Cole, G. F. (1994)
This study was undertaken to examine the dependence of the regulatory enzymes of photosynthetic induction on photon flux density (PFD) exposure in soybean (Glycine max L.). The induction state varies as a function of both the magnitude and duration of the PFD levels experienced prior to an increase in PFD. The photosynthetic induction state results from the combined activity of separate processes that each in turn depend on prior PFD environment in different ways. Direct measurement of enzyme activities coupled with determination of in situ metabolite pool sizes indicated that the fast-induction component was associated with the activation state of stromal fructose-1,6-bisphosphatase (FBPase, EC 3.1.3.11) and showed rapid deactivation in the dark and at low PFD. The fast-induction component was activated at low PFD levels, around 70 [mu]mol photons m-2 s-1. Ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco, EC 2.7.1.19) deactivated very slowly in the dark and required higher PFD for activation. Both enzymes saturated at lower PFD than did photosynthesis, around 400 [mu]mol photons m-2 s-1. Ribulose-5-phosphate kinase (EC 2.7.1.19) appeared never to be limiting to photosynthesis, and saturated at much lower PFD than either FBPase or Rubisco. Determination of photosynthetic metabolite pool sizes from leaves at different positions within a soybean canopy showed a limitation to carbon uptake at the stromal FBPase and possibly the sedoheptulose-1,7-bisphosphatase (EC 3.1.3.37) in shade leaves upon initial illumination at saturating PFD levels.